2002
DOI: 10.1007/s10350-004-6190-4
|View full text |Cite
|
Sign up to set email alerts
|

Self-Expandable Stent Before Elective Surgery vs . Emergency Surgery for the Treatment of Malignant Colorectal Obstructions: Comparison of Primary Anastomosis and Morbidity Rates

Abstract: In our patients with left-sided malignant colon and rectal obstruction, placement of a preoperative stent prevented 17 (94 percent) of 18 of unnecessary operations and a large number of colostomies after elective surgery. These results were obtained with a lower severe complication rate as well as a shorter hospital stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
142
4
11

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 243 publications
(164 citation statements)
references
References 16 publications
4
142
4
11
Order By: Relevance
“…Treatment with dolantin was not satisfactory, and venous injection of omeprazole and peridural anesthesia were used for 2 days to relieve the pain. In terms of pain after stent placement, the incidence (16.7%) was slightly higher than those reported previously [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] . This may be attributable to the types of lesions and size of the stents.…”
Section: Discussionmentioning
confidence: 61%
“…Treatment with dolantin was not satisfactory, and venous injection of omeprazole and peridural anesthesia were used for 2 days to relieve the pain. In terms of pain after stent placement, the incidence (16.7%) was slightly higher than those reported previously [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] . This may be attributable to the types of lesions and size of the stents.…”
Section: Discussionmentioning
confidence: 61%
“…primary anastomosis rates at least twice as high as those aft er emergency surgery and with a remarkable decrease in number of colostomies ( 20,21 ). Furthermore, placement of the SEMS allows the treating physician to perform a complete preoperative colonoscopy to exclude synchronous lesions ( 22 ) and to perform accurate tumoral staging -essential for determining the best therapeutic option for the patient, considering that up to 50 % of patients who undergo emergency laparotomy are not candidates for curative surgery ( 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…The use of stents as a bridge to surgery has been validated by studies 19,24,26 that have shown less morbidity, less stoma formation, and shorter hospital stays compared to emergency surgery for colorectal obstruction. Three studies have also demonstrated that stent placement is costeffective compared to surgery.…”
Section: Discussionmentioning
confidence: 99%